2019
DOI: 10.1093/ije/dyz191
|View full text |Cite
|
Sign up to set email alerts
|

Education inequalities in adult all-cause mortality: first national data for Australia using linked census and mortality data

Abstract: Background National linked mortality and census data have not previously been available for Australia. We estimated education-based mortality inequalities from linked census and mortality data that are suitable for international comparisons. Methods We used the Australian Bureau of Statistics Death Registrations to Census file, with data on deaths (2011–2012) linked probabilistically to census data (linkage rate 81%). To asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
2
24
2
Order By: Relevance
“…Compared with the most recent national estimates of inequalities (for the period 2009-11) using area-level measures of SEP, our education-based inequality estimates are substantially larger for all-cause and cause-specific mortality ( 11 ). Our estimates are also higher than but consistent with previous estimates of education-related inequalities reported for all-cause ( 6 ) and selected causes of death ( 26 ) in Australia for 2011-12. These differences likely reflect, at last in part, methodological differences, as well as changes in the composition of educational groups over time (Supplementary 5).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Compared with the most recent national estimates of inequalities (for the period 2009-11) using area-level measures of SEP, our education-based inequality estimates are substantially larger for all-cause and cause-specific mortality ( 11 ). Our estimates are also higher than but consistent with previous estimates of education-related inequalities reported for all-cause ( 6 ) and selected causes of death ( 26 ) in Australia for 2011-12. These differences likely reflect, at last in part, methodological differences, as well as changes in the composition of educational groups over time (Supplementary 5).…”
Section: Discussionsupporting
confidence: 89%
“…The RRs presented in this study are generally larger in magnitude than those reported for other high-income countries ( 8, 9, 27-29 ). However, similar estimates have been reported in other advanced welfare states ( 6, 2, 7, 28 ). In Norway, education-related mortality RRs for men in causes amenable to behaviour change were greater than three for the population aged 30-79, and were greater than two for causes amenable to medical intervention ( 8 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We derived highest level of education from two self-reported census variables: highest year of secondary school completed and highest non-school qualification. Consistent with OECD recommendations and in line with previous Australian research describing mortality inequalities according to education level [ 7 , 16 ], we created five mutually exclusive categories. These were: university qualification, irrespective of whether Year 12 was completed (highest education level); other post-secondary school qualification and completed Year 12; other post-secondary school qualification but did not complete Year 12; no post-secondary school qualification but completed Year 12; and, no post-secondary school qualification and did not complete Year 12 (lowest education level).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most prominent forms of health inequality relates to an individual's socioeconomic position, with well documented inequalities evident in numerous health indicators [4,5], including mortality [6,7]. Yet, there are no contemporary estimates of socioeconomic gaps in life expectancy for Australia.…”
Section: Introductionmentioning
confidence: 99%